(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2011)
There is a wide range of demand on Lagos as an urban centre and pragmatic approaches to complement the urbanization process and its attendant problems need urgent attention. The dynamism of Lagos as an urban centre cannot be stopped, but precautionary measures can be taken to nip the bud in the anticipated fallouts of this trend. The paper examines the urbanization, housing and the dearth of infrastructure in Lagos. Although the city of Lagos has over the years sprawled and has become a mega city, with the symptoms of urbanization being inadequately supplied. The paper further examines the provision of infrastructure in Lagos in the last decade. The government had commenced a total rebirth of the entire gamut of decay and social disintegration through the provisions of basic infrastructure. Projects executed by the state government with respect to urbanization, housing and infrastructure were examined. And recommendations on how to further meet future challenges in Lagos with regard to urbanization were proffered